Análisis de las referencias sobre acuicultura en Costa Rica 1970-1994 (ING) - Günther, Jorge (Uniciencia, 1994)
360 costarican references on aquacultural subjects from the period 1970 to 1994 were collected. The references were classified and analyzed by type of publication, general thematics, publication date, involved institutions, animal species, authors and journals.